THE LIFE CYCLE ASSESSMENT - A CASE STUDY OF TRANSPORTING VOLVO CARS - Gloria P. Gerilla (Institute of Research and Community Outreach - Petra Christian University, 2000)
The increase in the number of vehicles in our society is detrimental to the environment because of increased fuel usage and pollutant emissions. This paper analyze the environmental effects of transporting cars from its manufacturer to its end user. The method used is the life cycle assessment (LCA). Life cycle assessment is a method for analyzing and evaluating environmental performance of products, processes or services throughout its entire life cycle. The paper also shows the effect of changing the fuel type used in transporting the vehicles. It can be seen that from the pollutant emissions in the transport chain, carbon dioxide and nitrogen oxides are the leading pollutants, which affect the air quality in the environment. The truck is shown to be a heavy polluter in terms of its emission factors and there is not much difference between a European and an Asian country. With the use of the natural gas as an alternative fuel, emission levels can be reduced to as much as 19 % for CO2 and 16 % for NOx emissions while costs are higher in the first few years because of conversion costs, it can be said that it is worth the risk. The truck can be an environmentally adapted vehicle if its engine is converted to an alternative fuel engine like the compressed natural gas. The LCA methodology is holistic because it gives a systems analysis of the product